Argumentation and the Force of Reasons - Robert C. Pinto (Informal Logic, 2009)
Argumentation involves offering and/or exchanging reasons – either reasons for adopting various attitudes towards specific propositional contents or else reasons for acting in various ways. This paper develops the idea that the force of reasons is through and through a normative force because what good reasons accomplish is precisely to give one a certain sort of entitlement to do what they are reasons for. The paper attempts to shed light on what it is to have a reason, how the sort of entitlement arising from reasons differs from other species of entitlement and how the norms by which such entitlement is assessed obtain their status as norms.